Multiphase magmatic overprinting in the Late Jurassic Laoniushan pluton at the SW margin of the North China Craton: Geochronological and petrogenetic constraints. (13th April 2020) - Yang, Chunsi; Chen, Huayong; Zhao, Liandang; Jiang, Hongjun; Wang, Dequan; Zheng, Hui; Han, Jinsheng; Wu, Chao; Lai, Chunkit
Abstract : Late Mesozoic granitoids are widely emplaced in the Qinling Orogen on the southern margin of North China Craton (NCC), and can provide important clues on the Late Mesozoic regional geodynamic setting. The Late Jurassic Laoniushan granitic pluton is located in the western end of the southern NCC margin. Zircon U–Pb dating for the granodiorite, quartz diorite, and biotite monzogranite of the pluton yielded 152.5 ± 1.6 Ma, 148.7 ± 1.2 Ma, and 149–146 Ma, respectively. Compilation of the single zircon ages revealed magmatic peaks at ca. 146, 152, and 163 Ma, suggesting multiphase Late Jurassic magmatism. These granitoids are high‐K calc‐alkaline, I‐type, and metaluminous to weakly peraluminous. The rocks show chondrite‐normalised LREE enrichments, HREE depletions and flat HREE patterns, together with (slightly) negative Eu, Nb, Ta, P, and Ti anomalies. The Laoniushan granodiorite and biotite monzogranite have similar REE patterns to the quartz diorite, but the former two have much smaller Eu anomalies than the latter. The negative zircon ε Hf ( t ) (−32.6 to −13.7), ε Nd ( t ) (−20.7 to −14.3) and crustal‐like whole‐rock trace‐elemental ratios (e.g., Nb/Ta, Th/U, Nb/U, and Ce/Pb), together with the low Mg (MgO = 0.18–2.02 wt%, Mg # = 20–34), Cr (7.00–39.0 ppm), and Ni (0.80–4.00 ppm) contents, suggests that the Late Jurassic granitoids were probably derived from the partial melting of ancient crustal rocks with minor mantle‐derived input. The granodiorite and quartz diorite have similar average ε Hf ( t ) (−26.5 and −26.7, respectively), ε Nd ( t ) (−20.5 and −20.2, respectively), T DM2 (Hf) (2880 and 2885 Ma, respectively) and T DM2 (Nd; 2607 and 2578 Ma, respectively), whereas the biotite monzogranite has higher average ε Hf ( t ) (−17.1) and ε Nd ( t ) (−15.3), and younger T DM2 (Hf) (2281 Ma) and T DM2 (Nd) (2176 Ma). This suggests that the biotite monzogranite has different magma sources and shallower magma formation depths compared to the granodiorite and quartz diorite. The latter two were likely formed by the partial melting of continental crustal rocks (notably the Taihua Group basement rocks), which was triggered by mantle underplating led by asthenospheric upwelling. The Late Jurassic Laoniushan granitoids may have formed in an extensional setting caused by the Palaeo‐Pacific Plate subduction beneath Eastern China. Commencement of Late Jurassic Laoniushan granitic magmatism likely marked the incipient of lithospheric thinning along the southern NCC margin. Considering also the regional geological evolution, we conclude that although the Laoniushan pluton exhibits spatial–temporal relationships with the nearby Mo (–U) and REE deposits, there is still no unambiguous metallogenic link with these deposits.